First record and ecologic aspects of Isthmochloron neustonica Zalocar & Pizzarro (Tribophyceae) in São Paulo State, Brazil1 - Osti, João Alexandre Saviolo [UNESP]; Tucci, Andréa; Camargo, Antonio Fernando Monteiro [UNESP] (Instituto de Botânica, 2016)
We present the morphometric characteristics of Isthmochloron neustonica populations as well as their abundance and the relationship with some environmental characteristics in a fishpond. This is the first record of the species in São Paulo State and second citation to Brazil. Isthmochloron neustonica was described in neustonic habit; in this study, with sampling for phytoplankton analysis, it was found in high density and short duration blooming (time interval up to 15 days). It represented 59% of total phytoplankton density on May 26, 2010, forming a delicate and bright film on the water surface, in an environment with high concentration of nutrients and associated with drought and low temperature. The species has a restricted range in South America, probably due to their biological characteristics, such as small cell size and neustonic habit. Few records in literature can also be one of the reasons that hampers the identification of the species in subtropical environments.

Apresentamos as características morfológicas de populações de Isthmochloron neustonica bem como, sua abundância e a relação com algumas características ambientais em tanque de piscicultura. Trata-se do primeiro registro da espécie para o Estado de São Paulo e segunda citação para o Brasil. Isthmochloron neustonica foi descrita com hábito neustônico e no presente estudo, com amostragem para análise do fitoplâncton, foi registrada com elevada densidade, caracterizando floração de curta duração (intervalo de tempo de 15 dias), representando 59% da densidade total fitoplanctônica em 26 de maio de 2010, formando sobre a superfície da água uma película delicada e brilhante, em ambiente com alta concentração de nutrientes e no período seco e baixa temperatura. A espécie apresenta distribuição geográfica restrita a América do Sul, provavelmente em função de suas características biológicas, como células de pequeno tamanho e hábito neustônico, os poucos registros na literatura, pode dificultar a identificação e o registro da espécie em ambientes subtropicais.
Keywords: Ecology; freshwater; taxonomy; Água doce; ecologia; taxonomia